Dynamic Effects of the Underground Squat Silo during Symmetic Discharging with Different Static Friction Coefficients - JIN Li-bing; ZHANG Jing-jin; WANG Xu; ZHU Dou-dou; LIU Yue-fang (Liang you shipin ke-ji)
Underground squat silos can utilize shallow geothermal energy to realize natural quasi-low temperature storage to ensure the grain quality, which is a suitable warehouse for green grain storage. A combined approach of numerical simulation and theoretical analysis was employed to investigate the influence of the static friction coefficient between grain particles on the dynamic response of the interaction between grain particles and the silo wall during symmetric discharging in underground squat silos. The mathematical analysis model of the underground squat silo is constructed using the discrete element method. The effectiveness of the numerical analysis method is verified by comparing the numerical analysis results with the theoretical calculation. The dynamic response of the silo wall and the grain particles at different static friction coefficients was then numerically analyzed, and the dynamic pressure of the silo wall, the unloading rate, and the contact stress and velocity distribution between the grain particles at different static friction coefficients were studied. The results show that: the dynamic pressure and the unloading rate of the silo wall gradually decrease with the increase of the static friction coefficient; furthermore, the horizontal and vertical contact stresses and the velocities between the grains increase with the increase of static friction coefficient. These findings contribute to a comprehensive understanding of the dynamic performance of underground squat silos during unloading and offer insights for the optimal design of their structures.